SIFAT DAN MUTU ARANG AKTIF TEMPURUNG KEMIRI - Mody Lempang; Wasrin Syafii; Gustan Pari (BRIN Publishing, 2012)
Activated charcoal is charcoal product obtained through activating process which possesses better adsorption properties and wider uses than charcoal. The common sources of activated charcoal feedstocks are coal, wood and agricultural by-products such as nutshells and fruitpits. This research was carried out to develop processing technology of cundienut shell activated charcoal. Candlenut shell (Aleurites moluccana Willd) were carbonised in drum kyln to produce charcoal, then the charcoal was activated in electrical retort beating duration of 90 and 120 minuts at temperatur of 550 C, 650 C and 750 C. Properties evalnation were assessed in a accord with the Indonesia National Standard (SNI) 06-3730-1995. Results indicated that the activation treatment bad direct affect on the activated charcoal properties. The activated charcoal that efforded highest adsorption capacity on lodine number of 758,70 mg/g wat optained by steaming activation could meet at temperatur of 750 C. This activated charcoal properties the requirements of SN106-3730-1995,